Q&A: ICTs and forest certification - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Forest certification is a relatively new means of promoting sustainable forest management. The most widely used certification system is managed by the Forest Stewardship Council (FSC) in Bonn, Germany. Zandra Martinez explains how the FSC is using ICTs to